Spatial econometrics using microdata - Dubé, Jean; Legros, Diego (GIS and territorial intelligence, 2014)
The objective of this book is to make a link between existing quantitative approaches... and the manner in which we can generalize thess approaches to cases where the available data for analysis have a spatial dimension.